Co-infections and Pathogenesis of KSHV-Associated Malignancies - Thakker, Suhani; Verma, Subhash C. (Frontiers in Microbiology, 2016)
Kaposi’s sarcoma-associated herpesvirus (KSHV), also known as human herpes virus 8 (HHV-8) is one of the several carcinogenic viruses that infect humans. KSHV infection has been implicated in the development of Kaposi’s sarcoma (KS), primary effusion lymphoma, and multicentric Castleman’s Disease. While KSHV infection is necessary for the development of KSHV associated malignancies, it is not sufficient to induce tumorigenesis. Evidently, other co-factors are essential for the progression of KSHV induced malignancies. One of the most important co-factors, necessary for the progression of KSHV induced tumors, is immune suppression that frequently arises during co-infection with HIV and also by other immune suppressants. In this mini-review, we discuss the roles of co-infection with HIV and other pathogens on KSHV infection and pathogenesis.